50th AIAA Aerospace Sciences Meeting Including the New Horizons Forum and Aerospace Exposition 2012
DOI: 10.2514/6.2012-441
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Generalized Minimum Residual Krylov Subspace Method for Chemically Reacting Flows

Abstract: Two independent implementations of the Generalized Minimum Residual (GMRES)technique have been tested in the chemically reacting DPLR CFD code. The first implementation utilizes the existing Jacobian matrices by writing a new GMRES solver that is integrated directly into the DPLR CFD code time integration subroutine. The second implementation makes calls to the Portable, Extensible Toolkit for Scientific Computation (PETSc), an external linear and non-linear solver package, to perform the GMRES calculation. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…In general, 10 subiterations may not be sufficiently general (e.g., Ref. [21]). An alternative strategy pursued in the StMG solver is to specify targets for reduction in the L 2 -norm of the residual of the linear system.…”
Section: Iiie Relaxation Schemementioning
confidence: 99%
“…In general, 10 subiterations may not be sufficiently general (e.g., Ref. [21]). An alternative strategy pursued in the StMG solver is to specify targets for reduction in the L 2 -norm of the residual of the linear system.…”
Section: Iiie Relaxation Schemementioning
confidence: 99%
“…In a review of factorisation methods for CFD applications, Saad et al [134] found that no single method was superior to the rest. For hypersonic flows, a zero-fill Incomplete Lower-Upper (ILU) factorisation of an approximate first-order flow Jacobian has shown good results for inviscid, laminar and turbulent flows [135][136][137]. An ILU factorisation of a matrix is a sparse approximation of the LU factorisation; zero-fill denotes that the sparsity pattern of the ILU factorisation is that of the original matrix.…”
Section: Preconditioningmentioning
confidence: 99%